An Integrated Teaching and Learning Program in Pharmacology for Nursing Students. - Manias, Elizabeth; Bullock, Shane; Bennett, Rhonda ([Committee for the Advancement of University Teaching], 1995)
Report on a project with second year students in undergraduate nursing courses at RMIT University and Australian Catholic University. The project sought to help students make better links between scientific and nursing knowledge of pharmacology, and then to make clinical applications based on this knowledge. The initiative provided a necessary bridge between basic science and nursing subjects undertaken in first year, and the more specialised clinical science and nursing subjects of second year. It introduced a teaching innovation, consisting of a CD-ROM containing three simulated clinical scenarios and a teaching guide. The materials focused on three medical conditions that students encounter in clinical practice (asthma, congestive cardiac failure and diabetes mellitus) and their respective drug therapies.